Effect of alum-cationic rosin consumption level on the properties of papers made from recycled white sheets trimmings - Fatemeh Naijian (Regional Information Center for Science and Technology (RICeST), 2017)
Nowadays, recycled fibers are the main fiber source for manufacturing packaging papers. Sizing of such papers, based on the type of application, is of great importance. In this research, the effect of alum-cationic rosin consumption amount in pH of about 6.5 on the properties of papers made from white sheets trimmings was examined. In order to optimize consumption extent, pulp suspension sizing with alum in six level of 0, 4, 5, 7, 8, and 10 %, and rosin with the ratio of 50 % of alum based on oven dry (OD) pulp was done according to the TAPPI standard methods. Then by preparation of handsheets with basis weight of about 65±5 g/m2, their Cobb test (45 second), structural and strength characteristics were investigated. Statistical analysis of the results have shown that alum and rosin consumption amount of about 7 and 3.5 % based on OD pulp is the best suitable level for internal sizing of white sheets trimmings fibers. In these alum-rosin level, Cobb value of papers decreased from 120±11.6 g/m2 the lowest value of about 64±9.7 g/m2. Contact angle of water droplet with the paper surface increased from 24.81º to 96.53º. Paper tensile index decreased up to 125±9.7 N.m/g by such sizing level and again increased with increasing alum-rosin level. Seemingly, such phenomena can be attributed to the alum role in charge neutralizing, cellulosic fines retention and improving bonding-ability of paper network. Meaningful decrease of paper surface roughness from 10.34±0.54 µm in control sample to 8.23±1.37 µm in sized papers in optimized level confirmed this assumption.